2022
DOI: 10.3389/fpsyt.2022.960830
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between care burden, resilience, and depressive symptoms among the main family caregivers of stroke patients: A cross-sectional study

Abstract: ObjectivesThis study aims to explore the potential mediating role of resilience between care burden and depressive symptoms in family caregivers of stroke patients.MethodsA cross-sectional study was conducted with a convenience sample involving 245 main family caregivers of stroke patients recruited from the neurology department of a Tertiary A hospital in China. Mediation analyses were conducted using the PROCESS macro (Model 4) for SPSS, applying the Bootstrap analysis with 5,000 samples and a 95% confidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 87 publications
2
1
0
Order By: Relevance
“…The positive correlation between depression and caregiving burden, as is proved in this study, has been demonstrated in a number of previous studies (Adelman et al, 2014 ; Seo and Park, 2019 ; Ahmad Zubaidi et al, 2020 ; Fang et al, 2022 ).…”
Section: Discussionsupporting
confidence: 87%
“…The positive correlation between depression and caregiving burden, as is proved in this study, has been demonstrated in a number of previous studies (Adelman et al, 2014 ; Seo and Park, 2019 ; Ahmad Zubaidi et al, 2020 ; Fang et al, 2022 ).…”
Section: Discussionsupporting
confidence: 87%
“…The overall mean resilience scores of spousal caregivers in this study, across all three time points, were lower than the CD‐RISC scores reported for the general population (80.4 ± 12.8) and primary caregivers (71.8 ± 18.4) by Connor and Davidson (2003). However, the CD‐RISC scores in this study were similar to those found in studies of family caregivers of stroke patients in North China (Fang et al., 2022) and family caregivers of patients with bipolar disorder in South China (Su et al., 2021). These results imply that caregivers reported moderately low resilience at the early stage of a sudden or unexpected serious health event.…”
Section: Discussionsupporting
confidence: 88%
“…To date, some studies have explored the association between caregiver burden and the severity of patients’ functional deficits ( 24 , 25 ). Yet, few studies have described the impact of depression symptoms on caregiver burden.…”
Section: Introductionmentioning
confidence: 99%